Postcolonial Discourse: Language Nonconformity in Pantomime - Jawad, Kamal Hasan (Dirasat: Human and Social Sciences, 2024)
Objective: Post-colonial Caribbean playwrights have often employed linguistic deviations as part of a deconstructive approach to challenge the presumed irrationalities of colonial narratives. These deviations, whether syntactic, semantic, or lexical, are not merely stylistic choices but serve specific goals. This study aims to delineate these types of deviations and understand the underlying objectives. Method: A qualitative-analytic methodology was adopted to analyze the linguistic deviations evident in Walcott’s "Pantomime." Results: The play displays a wide range of linguistic deviations, all working towards constructing a new post-colonial model of resistance. This model is adorned with Caribbean diction and accent, challenging dominant Western colonial narratives and interrogating established socio-political structures influenced by Western hegemony. Conclusions: The literary output of the Caribbean, especially in the post-colonial era, has been significantly influenced by linguistic deviations. Playwrights, through their works, present these deviations syntactically, semantically, and lexically, ultimately offering a literary model poised against the colonizer.